Optimization of Taman Pendidikan Al-Qur'an (TPA) "Darul Muhajirin" in BORNEO SKM Housing, Samarinda City - Hadi, Saipul; Pranajaya, Syatria Adymas; Juhairiah, Juhairiah (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The status of religious education in Indonesia is equivalent to education in general. Thus, religious education needs to optimize and improve performance so that religious education is noticed in terms of management and administration with education in general. This service aims to optimize the existence of the Taman Pendidikan Al-Qur’an (TPA) "Darul Muhajirin" institution. This service uses a method in the form of an Asset Based Community Development (ABCD) approach. Optimization of the results of this service can be categorized into two parts, the first in terms of institutional optimization, namely submitting of TPA unit numbers to special institutions (BKPRMI), and the second from the aspect of optimizing Human Resources is by involving teachers and TPA of managers in teaching staff training about TPA, as well as holding Seminar on Education Quality Management Systems. This dedication implies that optimizing Taman Pendidikan Al-Qur’an "Darul Muhajirin" could be a place to form early Qur'an cadres for children, especially in BORNEO SKM Housing, Samarinda City.